2016
DOI: 10.1080/23288604.2016.1234863
|View full text |Cite
|
Sign up to set email alerts
|

Putting Institutions at the Center of Primary Health Care Reforms: Experience from Implementation in Three States in Nigeria

Abstract: Within the last two decades, the Nigerian government has committed to strengthening its primary health care system, through reforms addressing institutional restructuring, deepening decentralized governance, and the incorporation of an alternative health care financing strategy. One of these reforms prescribed the establishment of state primary health care agencies/boards (SPHCDBs) as an integral part of the national health system, with the principal responsibility "for the coordination of planning, budgeting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…However, we caution against viewing these reforms as secondary or spillover effects of RBF interventions implemented as vertical programs. In line with Soucat et al, 15 we argue that RBF design and implementation should focus their attention on how they can contribute to the broader goal of health systems strengthening. We hope that the articles in this special issue bring home to the reader the importance of dynamic, everevolving intersections of RBF interventions with underlying health systems.…”
Section: Resultssupporting
confidence: 69%
“…However, we caution against viewing these reforms as secondary or spillover effects of RBF interventions implemented as vertical programs. In line with Soucat et al, 15 we argue that RBF design and implementation should focus their attention on how they can contribute to the broader goal of health systems strengthening. We hope that the articles in this special issue bring home to the reader the importance of dynamic, everevolving intersections of RBF interventions with underlying health systems.…”
Section: Resultssupporting
confidence: 69%
“…The pay for performance approach is increasingly becoming popular due to its potential to improve health systems [23] and promote equity in health service utilization [24] . A recent review reported that pay for performance schemes had been implemented in at least 23 African countries [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Case study 1: Primary health care governance reform -Nigeria Nigeria recently initiated an integrated primary health care (PHC) governance policy commonly known as PHC under one roof (PHCUOR). The policy aims to integrate all primary health care services, structures and subsystems under a single governance body at the subnational level (Odutolu et al, 2016). PHCUOR is premised on a theory of change derived largely from brainstorming by subject matter experts in the national capital city, funded by international donors.…”
Section: Introductionmentioning
confidence: 99%
“…PHCUOR is premised on a theory of change derived largely from brainstorming by subject matter experts in the national capital city, funded by international donors. Although endorsed by the national council on health for nationwide implementation (National Council for Health, 2011; Odutolu et al, 2016), a recent evaluation revealed that subnational governments not only exercised discretion as to how they implemented the policy, in some cases the policy was redesigned at the subnational level without recourse to the theory of change (Eboreime et al, 2017). This may have untoward implications on the anticipated impact of the policy reform.…”
Section: Introductionmentioning
confidence: 99%